Developing Micro, Small, and Medium Enterprises (MSMEs) Through External Facilitation and Internal Potential: A Case Study of The "Emping Jagung" Business Group - Azari Azari Putri (Indonesian Research of Sustainability Management, Business, & Administration (IRHAMNA), 2025)
This study examines the development of Micro, Small, and Medium Enterprises (MSMEs) through the combination of external facilitation and internal potential, using the corn-chip (“emping jagung”) business group in Pandanwangi Village, Blimbing District, Malang City, as a case study. Internally, the business group has strengthened its potential through self-financed capital, product innovation, marketing network expansion, and improvement of production facilities. Externally, the Malang City Cooperatives and SMEs Office has facilitated the group’s development by providing access to capital, coaching and training programs, product promotion activities, marketing network expansion, and supporting facilities and infrastructure. However, several persistent obstacles constrain business growth, including rising raw material prices, limited human resource capacity, capital-related difficulties, inadequate infrastructure, and restricted access to product marketing. This study employed a descriptive qualitative approach to identify, describe, and analyze both the developmental efforts and the obstacles faced by the business group. The findings indicate that although substantial support mechanisms exist, their impact remains constrained by uneven information dissemination, limited managerial capacity, and the absence of a dedicated MSME marketing network at the local government level.